2012
DOI: 10.1039/c1ee02262h
|View full text |Cite
|
Sign up to set email alerts
|

Novel insight into neutral medium as electrolyte for high-voltage supercapacitors

Abstract: This paper is focused on neutral aqueous medium, i.e. lithium, sodium and potassium sulfate solutions in a wide range of concentrations (0.1-2.5 mol L À1 ) as promising electrolytes for electrochemical capacitors because they are cheap, non-corrosive and allow applying diverse current collectors. These properties make the capacitor assembling process much easier and cheaper. Additionally, such electrolytes are electrochemically stable and environmentally friendly. Electrochemical investigations carried out esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
465
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 740 publications
(479 citation statements)
references
References 36 publications
12
465
2
Order By: Relevance
“…It has been reported that symmetric supercapacitors with wide voltage range, higher than the theoretical limit of water, can be overcome with pH-neutral electrolytic solutions of inorganic salts such as Li 2 SO 4 , Na 2 SO 4 and K 2 SO 4 with the Li 2 SO 4 being the most promising salt to date. 72 As explained by Fic et al, 72 the Li + and SO 4 2− ions are strongly solvated in the water molecules. The energy needed to decompose the water competes with the solvating energy.…”
Section: Resultsmentioning
confidence: 92%
“…It has been reported that symmetric supercapacitors with wide voltage range, higher than the theoretical limit of water, can be overcome with pH-neutral electrolytic solutions of inorganic salts such as Li 2 SO 4 , Na 2 SO 4 and K 2 SO 4 with the Li 2 SO 4 being the most promising salt to date. 72 As explained by Fic et al, 72 the Li + and SO 4 2− ions are strongly solvated in the water molecules. The energy needed to decompose the water competes with the solvating energy.…”
Section: Resultsmentioning
confidence: 92%
“…~2 V). Recently Fic et al [5] designed an activated carbon (AC) symmetric supercapacitor exhibiting a specific capacitance of 120 F.g -1 after 15 000 cycles in a working potential of 2.2 V in 1M Li 2 SO 4 aqueous electrolyte. Furthermore, novel asymmetric supercapacitors based on carbon in 1M H 2 SO 4 have demonstrated high stability after 10,000 cycles at 1.6 V [6].…”
Section: Introductionmentioning
confidence: 99%
“…We are also aware that most reported high-potential aqueous ECs used pH-neutral electrolytes. 16,34 To understand this phenomenon, we measure the potential of zero charge (PZC) for the carbon film electrodes in acidic or alkaline electrolytes before cycling. At pH 10, the measured PZC is −0.051 V vs Ag/AgCl (0.15 V vs SHE), while at pH 1, the PZC is 0.39 V vs Ag/AgCl (0.59 V vs SHE).…”
Section: Resultsmentioning
confidence: 99%
“…The electrolyte salts mater as well, where due to the strong solvation effect of Li + and SO 4 2− ions, ECs using a Li 2 SO 4 electrolyte can be cycled to 2.2 V in CV tests. 34 Very recently, Suo et al reported a "water-in-salt" aqueous electrolyte with 21 m LiTFSI in lithium-ion batteries, which can be polarized to 3.0 V. The high voltage is attributed to the reduced water activity due to the water coordination around Li + and the passivation effect from the reduced TFSI − ions. 35 Hydrogen electrosorption on nanoporous carbon electrodes is another approach to increase the effective charge storage.…”
Section: Vmentioning
confidence: 99%